Size and methylation mosaicism in males with Fragile X syndrome. (2nd November 2017) - Jiraanont, Poonnada; Kumar, Madhur; Tang, Hiu-Tung; Espinal, Glenda; Hagerman, Paul J; Hagerman, Randi J; Chutabhakdikul, Nuanchan; Tassone, Flora
ABSTRACT: Background: Size and methylation mosaicism are a common phenomenon in Fragile X syndrome (FXS). Here, the authors report a study on twelve fragile X males with atypical mosaicism, seven of whom presented with autism spectrum disorder. Methods : A combination of Southern Blot and PCR analysis was used for CGG allele sizing and methylation. FMR1 mRNA and FMRP expression were measured by qRT-PCR and by Homogeneous Time Resolved Fluorescence methodology, respectively. Results : DNA analysis showed atypical size- or methylation-mosaicism with both, full mutation and smaller (normal to premutation) alleles, as well as a combination of methylated and unmethylated alleles. Four individuals carried a deletion of the CGG repeat and portions of the flanking regions. The extent of methylation among the participants was reflected in the lower FMR1 mRNA and FMRP expression levels detected in these subjects. Conclusion : Decreased gene expression is likely the main contributor to the cognitive impairment observed in these subjects; although the presence of a normal allele did not appear to compensate for the presence of the full mutation, it correlated with better cognitive function in some but not all of the reported cases emphasizing the complexity of the molecular and clinical profile in FXS.